Genetics algorithms as a tuning tool for PID and sliding mode controllers - Juan Terán Picón; José Anderez; Oscar Camacho (Revista Técnica de la Facultad de Ingeniería, 2010)
In this paper, the genetic algorithms are used as a searching tool of the tuning parameters of a controller. The algorithm works such a way that the new tunings improve the performance of the control system. Two studied cases are considered: the first case is the proportional-integral-derivative controller and the second study case is the sliding mode controller. The algorithms are applied from initial tunings, such as Ziegler and Nichols for the PID controller and the obtained from Camacho for sliding mode controller